Development of Covid-19 Patient Data Submission Application at RT/RW (Sublocal/Local Area Governments) to Public Health Center Based on The Web - Acep Cahya Maulidi; Al-Atthur Rafly Muhammad; Cahyadi Agustin; Jaenal Arifin (Syntax Corporation, 2022)
Indonesia becomes one of the countries known with the highest positive cases of COVID-19 in the world. Every day there are new positive cases reported to the health facilities. Currently health facilities still use reporting data system for corona affected patient manually using files. This causes a lot of spaces used for storage or files which increases every day and affecs the service that becomes slower. The purpose of this research is to build an application that makes it easier for RT/RW in submitting and reporting data, and there is no need for in-person meetings to provide COVID-19 patient data to local health facilities. The development of this application uses an object-oriented modeling approach (UML) using the waterfall method. The programming languages used are PHP and javascript with Bootstap framework. The result of this research is a patient data reporting application that can facilitates health facilities in managing and increasing data validity to accelerate the handling of COVID-19 in Indonesia